Association of county perinatal resources and gestational weight gain in West Virginia, United States - Wilson A. Koech; Christa L. Lilly (BMC, 2019)
Abstract Background Inappropriate (inadequate or excessive) gestational weight gain (GWG) is of great concern to maternal, fetal and infant health. Different maternal and fetal risk factors are associated with GWG, but little is known about a more distal risk factor: inadequate county-level perinatal resources. Therefore, the study aim was to investigate GWG in women living in counties with below average perinatal resources in comparison with their counterparts living in counties with above average perinatal resources. Methods Retrospective study of 406,792,010-2011 West Virginia births in 55 counties. The outcome was GWG and the main predictor was county perinatal resources. Hierarchical linear mixed model was used to investigate the association of county perinatal resources and GWG. Results County perinatal resources was associated with GWG (p = 0.009), controlling for important covariates. Below average county perinatal resources was not significantly associated with a decrease in mean GWG (M: − 5.29 lbs., 95% CI: − 13.94, 3.35, p = 0.2086), in comparison with counties with above average county perinatal resources. There was significant difference between average, and above average county perinatal resources (M: − 17.20 lbs., 95% CI: − 22.94, − 11.47, p < 0.0001), controlling for smoking during pregnancy and other covariates. Conclusions Average county perinatal resources was associated with reduced mean GWG relative to above average county perinatal resources, but not below average county perinatal resources. However, this could be due to the small number of counties with above average resources as the effect was in the hypothesized direction. This highlights one of the challenges in county perinatal resource studies.